2021
DOI: 10.3390/ijms22031111
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a DNA Methylation Signature for the Intellectual Developmental Disorder, X-Linked, Syndromic, Armfield Type

Abstract: A growing number of genetic neurodevelopmental disorders are known to be associated with unique genomic DNA methylation patterns, called episignatures, which are detectable in peripheral blood. The intellectual developmental disorder, X-linked, syndromic, Armfield type (MRXSA) is caused by missense variants in FAM50A. Functional studies revealed the pathogenesis to be a spliceosomopathy that is characterized by atypical mRNA processing during development. In this study, we assessed the peripheral blood specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 10 These changes in DNA methylation, referred to as episignatures, are a functional consequence of disease-associated genetic variants and are emerging as highly accurate and stable biomarkers in a growing number of Mendelian disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Previous work by our group and others has demonstrated evidence of DNA methylation episignatures in a growing number of neurodevelopmental genetic disorders, which have previously been clinically validated as part of a diagnostic test called EpiSign. 15 , 29 , 30 These episignatures are particularly evident in disorders involving chromatin remodeling genes.…”
Section: Introductionmentioning
confidence: 99%
“… 10 These changes in DNA methylation, referred to as episignatures, are a functional consequence of disease-associated genetic variants and are emerging as highly accurate and stable biomarkers in a growing number of Mendelian disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Previous work by our group and others has demonstrated evidence of DNA methylation episignatures in a growing number of neurodevelopmental genetic disorders, which have previously been clinically validated as part of a diagnostic test called EpiSign. 15 , 29 , 30 These episignatures are particularly evident in disorders involving chromatin remodeling genes.…”
Section: Introductionmentioning
confidence: 99%
“…These methylation changes may be a direct consequence of the disruption of the gene function as in the chromatin remodeling, DNA methylation, and histone modification genes (Janssen & Lorincz, 2021; Sadikovic et al, 2019). More recent work has shown that changes in DNA methylation are also found in patients with pathogenic variants in genes that have no known direct role in DNA methylation or chromatin remodeling including FAM50A , UBE2A , and ZNF711 (Haghshenas et al, 2021; Levy et al, 2022). These indirect changes may be caused by perturbations in the interconnected molecular pathways, including transcriptional regulation and protein signaling, as opposed to directly by DNA methylases or demethylases.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the development of 56 distinct diagnostic episignatures encompassing 65 neurodevelopmental syndromes caused by pathogenic variants in 61 genes, and their use as highly sensitive and specific diagnostic biomarkers (Aref‐Eshghi, Bend, et al, 2018; Aref‐Eshghi, E., Rodenhiser, 2018; Aref‐Eshghi et al, 2017, 2020; Bend et al, 2019; Ciolfi et al, 2020, 2021; Haghshenas et al, 2021; Hood et al, 2016; Kerkhof et al, 2021; Krzyzewska et al, 2019; Levy et al, 2021, 2022; Radio et al, 2021; Rooney et al, 2021; Sadikovic et al, 2021; Schenkel et al, 2017, 2018, 2021). In these studies, we demonstrated that a monogenic syndrome may have more than one episignature depending on the location and/or functional consequence of the underlying genetic variant within the gene.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the detection of DNA methylation episignatures has gained the most popularity among epigenetic approaches for rare disease diagnosis. Several studies have shown that pathogenic variants in disease‐causing genes can induce stable changes in DNA methylation patterns at multiple positions across the genome, referred to as episignatures 131–141 . They are typically detected by conducting epigenome‐wide association studies and then training binary or multi‐class machine learning classifiers 142 .…”
Section: Dna Methylation Episignatures and Epivariationsmentioning
confidence: 99%
“…Several studies have shown that pathogenic variants in disease-causing genes can induce stable changes in DNA methylation patterns at multiple positions across the genome, referred to as episignatures. [131][132][133][134][135][136][137][138][139][140][141] They are typically detected by conducting epigenome-wide association studies and then training binary or multi-class machine learning classifiers. 142 To date, episignatures have been described for more than 65 Mendelian neurodevelopmental disorders.…”
Section: Dna Methylation Episignatures and Epivariationsmentioning
confidence: 99%